Function-driven design of Bacillus kochii and Filobasidium magnum co-culture to improve quality of flue-cured tobacco - Wu, Xinying; Cai, Wen; Zhu, Pengcheng; Peng, Zheng; Zheng, Tianfei; Li, Dongliang; Li, Jianghua; Zhou, Guanyu; Zhang, Juan; Du, Guocheng (Frontiers in Microbiology, 2023)
Flue-cured tobacco (FCT) is an economical raw material whose quality affects the quality and cost of the derived product. However, the time-consuming and inefficient spontaneous aging is the primary process for improving the FCT quality in the industry. In this study, a function-driven co-culture with functional microorganisms was built in response to the quality-driven need for less irritation and more aroma in FCT. The previous study has found that Bacillus kochii SC could degrade starch and protein to reduce tobacco irritation and off-flavors. The Filobasidium magnum F7 with high lipoxygenase activity was screened out for degrading higher fatty acid esters and terpenoids to promote the aroma and flavor of FCT. Co-cultivation with strain SC and F7 obtained better quality improvement than mono-culture at an initial inoculation ratio of 1:3 for 2 days, representing a significant breakthrough in efficiency and a reduction in production costs compared to the more than 2 years required for the spontaneous aging process. Through the analysis of microbial diversity, predicted flora functions, enzyme activities and volatile compositions within the mono- and co-cultivation, our study showed the formation of a function-driven co-culture between two strains through functional division of labor and nutritional feeding. Herein, the function-driven co-culture via bioaugmentation will become an increasingly implemented approach for the tobacco industry.